Political corruption in America : an encyclopedia of scandals, power, and greed - Grossman, Mark (Grey House Publishing, 2017)
This book covers the complete scandal-filled history of American political corruption, exploring the people, crimes, investigations and court cases behind 200 years of political scandals. It includes political cartoons, photos, graphs, and tables to provide additional context, as well as a historical chronology from colonial times to the present.